Pengaruh Sari Buah Merah (Pandanus conoideus Lam) terhadap Abnormalitas Spermatozoa Ayam Kampung - Tethool, Angelina Novita; Ollong, Abdul Rahman; Koibur, Johan Fredrik (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Antioxidants are substances that can prevent the occurrence of free radical antioxidation reactions in lipid oxidation. Red fruit (Pandanus conoideus Lam) is one of the plants endemic to Papua which contain high antioxidant. The aim of this research was to determine the abnormality spermatozoa of ayam Kampung which were received red fruit extract treatment. Eight cokcs were divided into 4 treatments, each treatment was repeated 5 times. The treatment consisted of control (P0) without extract, P1 with 0.5 mL extract/kgBW/day, P2 with 1 mL extract/kgBW/day and P3 with 1.5 mL extract/kgBW/day. The results showed that red fruit extract decreased the percentage of abnormality spermatozoa (P<0.05) compare to control (without red fruit extract). Forms of abnormality obtained was abnormalities on the head, namely swelled head, bent head, head detachement, knotted tail and smaller head, middle abnormalities, namely midpiece detachement and bending at midpiece border and abnormalities of the tail, namely bent tail, knotted tail, tail detachement and curled tail.